ANEMIA IN CHILDREN IN UKRAINE: A 24-YEAR RETROSPECTIVE ANALYSIS OF MORBIDITY AND PREVALENCE - Volosovets О.P.; Кryuchko T.O.; Kryvopustov, S.P.; Hubenko, I.Ya.; Loboda, A.M.; Kiselova, M.M.; Volosovets A.О.; Pavlyshyn, H.A. (World of Medicine and Biology, 2021)
The article is devoted to the growth of morbidity and prevalence of anemia in children of Ukraine in the period from 1994 to 2017. The methods of the system approach and epidemiological analysis of the MOH of Ukraine’s data in the period from 1994 to 2017 were used in the study. The retrospective study revealed that the incidence rate in children of Ukraine aged 0–17 inclusive increased by 31.4 % and by 59.8 % in the prevalence of anemia with their predominant detection in children affected by the Chernobyl accident and children constantly living in the areas with radiological control after the 1986 accident. A direct and noticeable relationship was established between the prevalence of anemia in children aged 0–14 years inclusive in 2011 and the population-weighted effective total radiation dose of the whole body in residents of different regions of Ukraine for the period 1997–2011 (p